PELABELAN TOTAL TAK REGULER PADA GRAF DISJOIN UNION LADDER RUNG DAN GRAF DISJOIN UNION DOMINO - Nugroho Arif Sudibyo; Ardymulya Iswardani; Yohana Putra Surya Rahmad Hidayat (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2020)
We investigate a graph labeling called the total vertex irregularity strength (tvs(G)). A tvs(G) is minimum for which graph has a vertex irregular total -labeling. In this paper, we determine the total vertex irregularity strength of disjoint union of ladder rung graph and disjoint union of domino graph.